Sex-on-premise venues, associated risk behaviors, and attitudes toward venue-based HIV testing among men who have sex with men in Lima, Perú - Alexander Lankowski; Hugo Sánchez; José Hidalgo; Robinson Cabello; Ann Duerr (BMC, 2020)
Abstract Background In Perú, HIV disproportionately affects men who have sex with men (MSM). Despite widespread access to treatment, the high rate of new HIV infections has remained unchanged over the last decade. Low knowledge of HIV status associated with late diagnosis is a key factor underlying the high HIV incidence observed in this setting, creating conditions for efficient onward transmission. Improving access to HIV testing and prevention services for those at highest risk is an important public health priority. Sex-on-premise venues (SOPVs) - saunas, sex clubs, pornographic movie theaters, hourly hotels, and bars/discos with areas where sex is permitted - may be opportune sites for outreach; however, further research on SOPVs and the populations who frequent them is needed to inform such efforts. Methods We conducted a cross-sectional online survey of adult MSM in Lima, Perú to evaluate patterns of SOPV attendance, associated sexual risk behaviors, and attitudes toward SOPV-based interventions. Participants were recruited through outreach to social media networks affiliated with local LGBTQ-aligned community groups. Our primary analytic objective was to estimate the association of HIV-related sexual risk behaviors and SOPV attendance. Additionally, we performed exploratory analyses to describe risk behavior stratified by SOPV category and to examine the relationship between SOPV attendance and the use of online platforms to meet sex partners. Results Overall, 389 MSM completed the survey from November 2018 through May 2019, of whom 68% reported attending an SOPV in the last 3 months. SOPV attendance was associated with multiple sexual risk behaviors, including transactional sex, group sex, substance use around the time of sex, and higher number of partners. Over two thirds of SOPV attendees indicated they would accept HIV testing if offered at SOPVs. Conclusions SOPV attendance was common among MSM in Lima who participated in our survey, and SOPV attendees reported significantly greater engagement in sexual risk behaviors related to HIV transmission. Attitudes toward hypothetical SOPV-based interventions were generally favorable. These findings suggest that outreach at SOPVs may be an effective mechanism for reaching a particularly high-risk sub-population of MSM in Perú to deliver targeted HIV testing and prevention interventions.